Enhanced electrocatalytic oxygen reduction reaction for Fe–N4–C by the incorporation of Co nanoparticles. Issue 13 (24th March 2021) - Jiang, Tao; Luan, Weiling; Turyanska, Lyudmila; Feng, Qi
Abstract : Co@Fe–N–C with the incorporation of Co nanoparticles on the surface of Fe–N4 –C is prepared using a novel assisted thermal loading method which shows greatly enhanced ORR activity when compared to Fe–N–C. Abstract : Oxygen reduction reaction (ORR) catalytic activity can be improved by means of enhancing the synergy between transition metals. In this work, a novel porous Fe–N4 –C nanostructure containing uniformly dispersed Co nanoparticles (CoNPs) is prepared by an assisted thermal loading method. The as-prepared Co@Fe–N–C catalyst shows enhanced ORR activity with a half-wave potential ( E 1/2 ) of 0.92 V vs. RHE, which is much higher than those of the direct pyrolysis CoNP-free sample Fe–N–C ( E 1/2 = 0.85 V) and Pt/C ( E 1/2 = 0.90 V) in alkaline media. It exhibits remarkable stability with only a 10 mV decrease in E 1/2 after 10 000 cycles and an outstanding long-term durability with 85% current remaining after 60 000 s. In acidic media, this catalyst exhibits catalytic activity with an E 1/2 of 0.79 V, comparable to Pt/C ( E 1/2 = 0.82 V). X-ray absorption fine spectroscopy analysis revealed the presence of active centres of Fe–N4 . Density functional theory calculations confirmed the strong synergy between CoNPs and Fe–N4 sites, providing a lower overpotential and beneficial electronic structure and a local coordination environment for the ORR. The incorporation of CoNPs on the surface of Fe–N4 –C nanomaterials plays a key role in enhancing the ORR catalytic activity and stability, providing a new route to prepare efficient Pt-free ORR catalysts.